2015
DOI: 10.1038/nature14490
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic diversity and evolutionary dynamics of Ebola virus in Sierra Leone

Abstract: The genome sequences of 175 Ebola virus from five districts in Sierra Leone, collected during September–November 2014, show that the rate of virus evolution seems to be similar to that observed during previous outbreaks and that the genetic diversity of the virus has increased substantially, with the emergence of several novel lineages. Supplementary information The online version of this article (doi:10.1038/nature14490) contains supplementary material, which is available to authoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
153
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(166 citation statements)
references
References 16 publications
11
153
0
Order By: Relevance
“…Finally, another hypothesis to consider is genetic variation of the virus. As described recently (15), isolates collected in Kailahun from July to November 2014 were shown to have become more phylogenetically and genetically diverse, resulting in the emergence of a multitude of novel lineages. Even though this diversification has not been linked to any phenotype of the virus (16), it could be the result of an adaptation of EBOV to its host, resulting in slower replication and a lower viremia.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, another hypothesis to consider is genetic variation of the virus. As described recently (15), isolates collected in Kailahun from July to November 2014 were shown to have become more phylogenetically and genetically diverse, resulting in the emergence of a multitude of novel lineages. Even though this diversification has not been linked to any phenotype of the virus (16), it could be the result of an adaptation of EBOV to its host, resulting in slower replication and a lower viremia.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of tracking sequence variation in relation to molecular detection strategies was highlighted in that analysis. More recent analysis, however, identified an observed evolutionary rate equivalent to that of past outbreaks [11].…”
Section: Discussionmentioning
confidence: 99%
“…The conserved regions in the ITS-5-based multiple sequence alignment were less than those based on the ITS-4-based multiple sequence alignment. For construction of a phylogenetic tree guided by parsimony values, the MrBayes method was used in a number of recent studies [17,18]. For building the phylogenetic tree, only the sequences generated using the ITS-4 primer were used because the multiple sequence alignment showed that all sequences obtained with this primer were more conserved than those amplified with the ITS-5 primer.…”
Section: Resultsmentioning
confidence: 99%